Identical steady tribological performance of graphene-oxide-strengthened polyurethane/epoxy interpenetrating polymer networks derived from graphene nanosheet. (1st May 2015) - Xia, Shaoling; Liu, Yingliang; Pei, Fuyun; Zhang, Linqi; Gao, Qiuju; Zou, Wenjun; Peng, Jin; Cao, Shaokui
Abstract: Graphene-oxide-hybrided polyurethane/epoxy interpenetrating polymer networks (PU/EP IPNs) are prepared through an in-situ polymerization. The results showed that the mechanical performance of graphene-oxide-hybrided PU/EP IPNs is improved due to the formation of chemical bonds between graphene oxide nanosheet and polyurethane/epoxy segments, affording the loading transfer from polymer matrix to graphene oxide nanosheet. The average friction coefficient in the steady stage is decreased about 30.2% from neat PU/EP IPN to graphene-oxide-hybrided PU/EP IPNs. Especially, the specific wear rate is decreased about two orders of magnitude from neat PU/EP IPN to graphene-oxide-hybrided PU/EP IPNs. Interestingly, graphene-oxide-hybrided PU/EP IPNs have the same friction coefficient in the steady stage, independent of graphene oxide content. The identical steady friction coefficients are derived from the same friction bodies in three-body friction model, such as graphene-oxide-strengthened PU/EP IPN surface, metallic counterpart and graphene-oxide-wrapping polymer particles as wear debris in the transfer film. Graphical abstract: Highlights: GO-hybrided PU/EP IPNs are prepared through an in-situ polymerization. The friction coefficient is decreased about 30.2% due to GO-hybridization. The specific wear rate is decreased about two orders of magnitude. The same friction coefficient in steady stage is obtained independent of GO content. The identical steady friction coefficients are derived from the same friction bodies.